Pelatihan Penyusunan Laporan Keuangan Badan Usaha Milik Gampong (BUMG) di Cot Mentiwan Kabupaten Aceh Besar - Umar, Zulkifli; Ermad M J; Dian Hendra Syahputra; Ricval Mawardi; Rusmelia (JPM: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service is to train managers of village-owned enterprises (BUMG) to be able to prepare financial reports. This is because BUMG managers are still experiencing problems in preparing financial reports. This activity provides solutions for BUMG managers so that their financial reports can be produced. This community service was carried out at BUMG Ban Na in Gampong Cot Mentiwan, Ingin Jaya District, Aceh Besar District. BUMG Ban Na is engaged in fattening cattle. The result of this community service is that it has succeeded 100% in making a BUMG Ban Na financial report for the year ending December 31, 2022.